Pengaruh Pemberian Jus Tomat (Lycopersicum Esculentum Mill) Terhadap Penurunan Kadar Kolesterol Low Density Lipoprotein (LDL) Dalam Darah Pada Pasien Dislipidemia Rawat Jalan Di RSUD Provinsi NTB - Juwita Nadia (Poltekkes Kemenkes Mataram, 2018)
Background. Dyslipidemia is defined as an abnormality of lipid metabolism which is characterized by an increase or decrease in the main lipid fractions, namely an increase in total cholesterol, Low Density Lipoprotein (LDL) cholesterol, triglycerides, and a decrease in plasma High Density Lipoprotein (HDL) cholesterol. Lycopene is one of the antioxidants that can affect lipid profiles. Research Methods. This research is a Pre-experimental research design pretest and posttest design. The subjects of this study were men and women aged ≥45 years with 8 people with LDL cholesterol levels> 100 mg / dl. Data were tested using the Paired T Test to determine the effect of decreasing LDL cholesterol levels before and after tomato juice administration (p = 0,000). Research Result. There was an average decrease of 20 mg / dl on LDL cholesterol levels before and after administration of tomato juice. Conclusion. There was a significant effect on the reduction of LDL cholesterol before and after being given an intervention in the form of tomato juice.